Mahuang Fuzi Xixin decoction ameliorates allergic rhinitis and repairs the airway epithelial barrier by modulating the lung microbiota dysbiosis - Wei, Xiaohan; Ding, Mengze; Liang, Xiao; Zhang, Baoping; Tan, Xiaomei; Zheng, Zezhong (Frontiers in Microbiology, 2023)
Background: Allergic rhinitis (AR) is a common disorder, that burdens general well-being. Although the lung is connected to the upper respiratory tract, which is rich in microorganisms, no studies have reported the relationship between lung microbiota and AR. Mahuang Fuzi Xixin decoction (MFXD) is a traditional Chinese medicine (TCM) formula that is widely used to treat AR in the clinic but its underlying mechanism remains unclear.We hypothesized that lung microbiota is associated with the pathogenesis of AR, and MFXD can improve AR by regulating microbiota dysbiosis.: The ovalbumin-induced mouse AR model was used to evaluate the therapeutic effect of MFXD on AR. Then 16S rDNA amplicon sequencing, untargeted metabolomics, and other molecular biology technology were used to clarify the effects of MFXD on lung microbes dysbiosis and AR progression. Further, the human nasal epithelial cell line (HNEpCs) was used to evaluate the protective effect of MFXD on epithelial barrier damage caused by specific pathogens Results: MFXD decreased plasma histamine and IgE levels, ameliorated pathological damage, and diminished the expression of tight junction proteins (ZO-1 and occludin) in lung and nasal tissues. MFXD altered AR-induced microbiota dysbiosis in the lungs and also plasma metabolites. Oral administration of MFXD altered microbiota dysbiosis in lung and AR-associated metabolic disorders. The dominant bacteria in the lungs of AR mice damaged the airway barrier, and MFXD reversed this change.Conclusions: This study revealed the correlation between the lung microbiota and AR in the mice model. We confirmed that lung microbiota plays a vital role in AR and that MFXD reduced damage to the epithelial barrier of the lungs and nasal mucosa by regulating lung microbiota and plasma metabolism imbalances. Our research provides a reference for the effect of lung microbiota on AR and provides a new idea for the treatment of AR.